Isospora belli Infection with Chronic Diarrhea in an Alcoholic Patient - Kim, Min Jae (The Korean Society for Parasitology and Tropical Medicine, 2013)
Chronic diarrhea with a 35 kg weight loss (75 kg to 40 kg) occurred during 2 years in an alcoholic patient was diagnosed with Isospora belli infection in the Republic of Korea. The patient, a 70-year old Korean male, had been a heavy drinker for more than 30 years. He was admitted to the Seoul National University Hospital because of long-standing diarrhea and severe weight loss. He had an increased white blood cell (WBC) count with high peripheral blood eosinophilia (36.8-39.9%) and lowered protein and albumin levels but without any evidence of immunosuppression. A parasitic infection was suspected and fecal examination was repeated 3 times with negative results. Peroral endoscopy with mural biopsy was performed in the upper jejunum. The biopsy specimens revealed villous atrophy with loss of villi together with various life cycle stages of I. belli, including trophozoites, schizonts, merozoites, macrogamonts, and microgamonts. The patient was treated successfully with oral doses of trimethoprim 160-320 mg and sulfamethoxazole 800-1,600 mg daily for 4 weeks. A follow-up evaluation at 2.5 years later revealed marked improvement of body weight (68 kg), increased protein and albumin levels, and normal WBC count with low eosinophils (3.1%). This is the first clinical case of isoporiasis with demonstration of various parasitic stages in the Republic of Korea.